PENERAPAN ARSITEKTUR REGIONALISME PADA TAMPILAN BANGUNAN BALAI LATIHAN KERJA KABUPATEN SLEMAN - Shalila Ariesta; Sumaryoto Sumaryoto; Tri Joko Daryanto (Universitas Sebelas Maret Surakarta, 2017)
Abstract :Economic globalization and trade, affect the qualification requirements and the types of labor are higher. Data from ministry of labor showed the competitiveness and productivity of labor in Indonesia relatively more low due to the low level of workforce education. Employment or Training Institute Training Center (BLK) is owned by Government Institutions, aims for the labor gets a chance to adding or sharpen work skills. The conditions of BLK Sleman previously still under minimum standards, whereas the interest and term of trainees are high enough. Redesign of exsisting building, making the BLK Sleman more optimal as the means and infrastructure to transform knowledge, skills and productive working, to improve the quality and competitiveness of Indonesian manpower. The design problem is to redesign BLK Sleman with architectural regionalism on the look of the building. The purpose of the redesign is to eksistence maintained of the training institute building and reflects the identity of the region. The design method used relate the architecturof the past and contemporary architecture by selecting one of the characteristics of traditional building details that are well known on the public.The result of the design can optimize and utilize the functions of BLK will be a credible, acceptable, and Independently institute through a system repair, methods, programs, facilities, and infrastructure with attention to the linkages between old building with new building. Keywords: Architectural Regionalism, Building Look, , Labor, Redesign, Sleman District, Training Center